Ionic Conductivity And Electrical Properties Of Carboxymethyl Cellulose - NH4CI Solid Polymer Electrolytes - Nur Hidayah Ahmad; Mohd Ikmar Nizam Mohamad Isa (School of Engineering, Taylor's University, 2024)
In this present work, carboxymethyl cellulose (CMC) - ammonium chloride (NH4Cl) solid polymer electrolyte (SPE) films were prepared by solution casting method. The ionic conductivity and electrical properties of SPE films were investigated using Electrical Impedance Spectroscopy. SPE film containing 16 wt. % NH4Cl exhibited the highest ionic conductivity of 1.43 x 10-3 S/cm at ambient temperature, 303K. The temperature dependence SPE films showed an Arrhenius-type relation where the regression values obtained from the log conductivity versus reciprocal temperature is close to unity (R2?1). The electrical properties have been measured as a function of frequency of Er, Ei, Mr, Mi shown a non-Debye type behavior.